Covid-19, Working from Home and the Potential Reverse Brain Drain - Irina Bakalova; Ruxanda Berlinschi; Jan Fidrmuc; Yuri Dzjuba (Center for Economic Studies and Ifo Institute (CESifo), 2021)
The COVID-19 pandemic has led to a substantial increase in the prevalence of working from home among white-collar occupations. This can have important implications for the future of the workplace and quality of life. We discuss an additional implication, which we label reverse brain drain: the possibility that white-collar migrant workers return to live in their countries of origin while continuing to work for employers in their countries of destination. We estimate the potential size of this reverse flow using data from the European Labor Force Survey. Our estimates suggest that the UK, France, Switzerland and Germany each have around half a million skilled migrants who could perform their jobs from their home countries. Most of them originate from the other EU member states: both old and new. We discuss the potential economic, social and political implications of such reverse brain drain.
Keywords: F22; J24; O15; 330; Covid-19; working from home; return migration; brain drain